Acetylation changes tau interactome to degrade tau in Alzheimer's disease animal and organoid models. Issue 1 (25th November 2019) - Choi, Heesun; Kim, Haeng Jun; Yang, Jinhee; Chae, Sehyun; Lee, Wonik; Chung, Sunwoo; Kim, Jisoo; Choi, Hyunjung; Song, Hyeseung; Lee, Chang Kon; Jun, Jae Hyun; Lee, Yong Jae; et al.
Abstract: Alzheimer's disease (AD) is an age‐related neurodegenerative disease. The most common pathological hallmarks are amyloid plaques and neurofibrillary tangles in the brain. In the brains of patients with AD, pathological tau is abnormally accumulated causing neuronal loss, synaptic dysfunction, and cognitive decline. We found a histone deacetylase 6 (HDAC6) inhibitor, CKD‐504, changed the tau interactome dramatically to degrade pathological tau not only in AD animal model (ADLP APT ) brains containing both amyloid plaques and neurofibrillary tangles but also in AD patient‐derived brain organoids. Acetylated tau recruited chaperone proteins such as Hsp40, Hsp70, and Hsp110, and this complex bound to novel tau E3 ligases including UBE2O and RNF14. This complex degraded pathological tau through proteasomal pathway. We also identified the responsible acetylation sites on tau. These dramatic tau‐interactome changes may result in tau degradation, leading to the recovery of synaptic pathology and cognitive decline in the ADLP APT mice. Abstract : In AD, as overall level of acetylation is down‐regulated, interactions of tau with indicated chaperones and E3 ligases may be insufficient to degrade pathologic tau and hardly degraded by UPS and become aggregated. CKD‐504, an HDAC6 inhibitor, elevates interactions of tau with chaperones and E3 ligases through increasing acetylation of each protein, resulting in ubiquitination and degradation of tau by UPS. Finally, degradation of tau rescues cognitive impairment in AD model mice.